PEMBERIAN HAK MILIK SATUAN RUMAH SUSUN DIATAS BEBERAPA HAK GUNA BANGUNAN PERORANGAN - Masrofah Masrofah (Badamai Law Journal, 2016)
The objectives of this research are: (1) to study and analyze the status of ownership of a modern shopping center or mall upon some tenure individual rights. (2) to study and analyze the process of grantingownership rights for apartment unit.The method used in this research was normative, that is, a legal research which was based on legal materials obtained from literature that examined legal norms related to the issue of providing ownership rights for apartment units upon some building rights.Based on the results of research and discussion, it can be concluded as follows: (1) PT. G.U. that wanted to have its apartment units certified for ownership had constraints by the absence of  implementation guidelines of Law No. 16 of 1985 (now Act No. 20 of 2011). (2) The principle of horizontal separation is the opposite of attachment principle which states that buildings and plants are integrated to land. (3) In planning the development of apartment, developers of the construction should first pay attention to the layout of the area of city/ county. (4) The construction of a housing project must meet some requirements, they are: administrative requirements, technical requirements and ecological requirements. (5) Prior to certificate of ownership registration upon an apartment unit, certificate of land rights either in the form of property rights, the right to use the land for building and the right to use and manage the land. (6) In the Act of Apartment, if it does not meet the provisions of these rules, there are some sanctions to be given. These may be in the form of administrative sanctions or criminal verdicts such as fines and imprisonment.Keywords: Granting Rights, Certificate of Ownership Rights Unit of the Flats, Broking,Transitional sale, Land Consolidation.